TAX, DEBT COVENANT AND EXCHANGE RATE (ANALISIS ATAS FENOMENA TRANSFER PRICING) - Tjandrakirana, Rina; Diani, Erma (Universitas Muhammadiyah Palembang, 2020)
This research was conducted because of the research gap between previous studies. The purpose of this study was to determine the effect of taxes, debt covenants and exchange rates on the company's decision to transfer pricing. This research was conducted on all manufacturing companies listed on the Indonesia Stock Exchange (IDX). The analysis technique used is quantitative descriptive analysis.The results of this study are that tax does not affect the company's decision to apply transfer pricing. This shows that the existence of a large tax burden will not make the company decide to implement transfer pricing. Debt covenant has a significant negative effect on the company's decision to apply transfer pricing, which shows that the lower debt to equity ratio (DER) will make the company decide to implement transfer pricing.While the exchange rate has a significant negative effect on the company's decision to implement transfer pricing. These results indicate that the lower the exchange rate will make the company decide to implement transfer pricing